Factors that Influence the Existence of Palace Cultural Tourism in the Era of Globalization - Mutia Ekasari, Astri; Rochman, Gina Puspita; Agustina, Ina Helena; Damayanti, Verry (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
Cirebon City has a lot of cultural heritage in the form of the Palace and other historical relics. The Department of Tourism and Culture of West Java Province tries to preserve the existence of this cultural heritage through the establishment of the History of the Palace as a primary tourist attraction. This study aims to determine the factors that influence the existence of historical palace tourism among the people in the current era of globalization. The research approach method is quantitative statistics, analyzing data with factor analysis. Data collection techniques were carried out through the distribution of online questionnaires. Respondents who were netted were 131 respondents from Cirebon City, Cirebon Regency, and Bandung City in the age range < 20 years to > 60 years. The results of the study concluded that the existence of the historical tourist attraction of the palace was known by most of the respondents. The government and managers of historical tourism and palaces can increase their existence and increase tourist visits by considering these four factors : Applications & Tourist Attractions, Historic Buildings & Traditional Ceremonies, Traditional Culinary, Superior Value.